Evaluation of the history of industrial plantation in Turkey - Erkan, Neşat ([TR] Orman Genel Müdürlüğü, 2021)
One of the important components of the forestry sector is forest industry organizations. The raw material requirement of these organizations is one of the important fields of activity of the sector. Therefore, special effort has been initiated since the 1960s in order to meet the increasing raw material needs with the proliferation and growth of forest industry organization in Turkey. These efforts, which started with the establishment of the Poplar Research Institute in İzmit, continued with introducing of some fast-growing species tree species, establishment of research trials and plot applications. Later, the subject was analyzed in depth with scientific meetings held in 1971, 1982, 1998 and 2003, and serious decisions were taken regarding the initiation of industrial afforestation, but these decisions could not be fully implemented until 2012. The most important implementation on the subject was implemented with the “Industrial Afforestation Works Action Plan” covering the period 2013-2023, prepared by the General Directorate of Forestry. However, there are still problems in this regard, especially arising from lack of awareness. With this study, the process experienced in industrial afforestation works in Turkey was evaluated and suggestions regarding the existing problems were developed.

Ormancılık sektörünün önemli bileşenlerinden birisi de orman endüstri kuruluşlarıdır. Bu kuruluşların hammadde ihtiyacı sektörün önemli faaliyet alanlarından birisidir. Nitekim ülkemizde orman endüstri kuruluşlarının çoğalması ve büyümesi ile birlikte artan hammadde ihtiyaçlarının karşılanması için 1960 lı yıllardan itibaren özel çabalar başlatılmıştır. İzmit’te Kavakcılık Araştırma Enstitüsü’nün kurulması ile başlayan bu çabalar bazı hızlı büyüyen ağaç türlerinin ithal edilmesi, araştırma denemelerinin kurulması ve plot uygulamaların yapılması ile devam etmiştir. Daha sonra 1971, 1982, 1998 ve 2003 yıllarında düzenlenen bilimsel toplantılarla konu derinlemesine analiz edilmiş ve endüstriyel ağaçlandırmaların başlatılması ile ilgili ciddi kararlar alınmış, ancak bu kararlar 2012 yılına kadar tam anlamıyla uygulamaya geçirilememiştir. Konu ile ilgili en önemli uygulama Orman Genel Müdürlüğü tarafından hazırlanan ve 2013-2023 dönemini kapsayan “Endüstriyel Ağaçlandırma Çalışmaları Eylem Planı” ile hayata geçirilmiştir. Ancak bu konuda, özellikle bilinç eksikliğinden kaynaklanan ve halen yaşanmakta olan sorunlar vardır. Bu çalışma ile ülkemizde endüstriyel ağaçlandırma çalışmalar konusunda yaşanan süreç değerlendirilmiş ve mevcut sorunlar ile ilgili öneriler geliştirilmiştir.
Geçmişten günümüze Türkiye’deki endüstriyel ağaçlandırma çalışmalarının değerlendirilmesi
Keywords: Forest Industry Engineering; Orman Endüstri Mühendisliği